PENINGKATAN KEMAMPUAN BERBAHASA INDONESIA MELALUI METODE DRAMA PADA SISWA KELAS VIIC SMP DHARMA PRAJA - juni ardianta (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Indonesian language skills are not only necessary in front of the class, upfront teacher or in front of friends. This capability is also used in all human activites daily, especially in conditions of formal. Student should be able to use the relevant Indonesian from early. Indonesian language skills VIIC grade students at the beginning of the assessment (Pretest) 86% is still below the minimum completeness criteria. Therefore in order grades VIIC can improve the ability to speak Indonesian the method used in this study is a drama that is formal. Of formal methods of drama students’ creativity in choosing diction and grammar with relevant Indonesian will increase. Improvement gained VIIC grade students in improving the relevant Indonesian language skills through drama methodes, namely by 93%. It shows that the method of formal drama is very effective in improving the relevant Indonesian language in class VIIC SMP Dharma Praja. Keywords: the ability to speak Indonesian and methods of drama